Understanding irrigation pump preferences in West Bengal: A paired comparison approach - Lountain, Sophie; Cooper, Bethany; Crase, Lin; Burton, Michael; Rigby, Dan (University of South Australia, 2023)
The impact of agricultural technology and access to this technology on the livelihoods of the rural poor cannot be overstated. It is crucial, however, to acknowledge that technology alone is not a panacea for poverty alleviation. While technological advancements offer immense opportunities, their effectiveness hinges on various factors, such as the diverse preferences of different user groups. This research provides valuable insights into the intricate relationship between energy, groundwater markets, and farmers’ preferences regarding groundwater pump technologies. Using primary field data from West Bengal, India, this study utilizes primary field data to shed light on the multifaceted dynamics that influence the livelihoods of impoverished farmers through the groundwater market. It employs a paired comparison technique, which provides a rigorous analysis of the diverse preferences of farmers regarding groundwater pump technologies. The findings underscore the significant variations in irrigation pump preferences among different farmer groups, emphasizing the need for tailored policies that consider the specific needs of each group. The study highlights that by aligning technology access with user preferences, policymakers can better facilitate inclusive development and equitable distribution of resources. It also sheds light on the interplay between irrigation technology, institutions and gender, revealing their substantial influence on the livelihoods of rural communities. In summary, this study finds that recognizing the difference in preferences and needs among farmers is essential for formulating effective policies that address the challenges faced by each group.